Circular economy meets smart energy grids: designing systems for resource optimization and carbon reduction - Munonye, Williams Chibueze (Frontiers in Sustainability, 2025)
This study examines the integration of Circular Economy (CE) principles with Smart Energy Grids (SEG) as a strategy to advance sustainable, low-carbon energy systems. The CE emphasizes minimizing waste, recovering resources, and prolonging material lifecycles, while SEG focuses on improving energy efficiency, supporting renewable energy integration, and enhancing grid resilience. These frameworks offer significant potential for optimizing resource use and reducing environmental impacts in the energy sector. However, several challenges hinder their full integration, such as technological barriers, regulatory constraints, and the lack of market incentives. Technological obstacles include the need for advanced recycling and energy storage solutions, particularly for renewable energy systems and electric vehicles. Regulatory frameworks are often insufficiently adaptable to the decentralized energy systems central to both CE and SEG. Additionally, policy frameworks that incentivize circular practices in energy infrastructure are essential for fostering innovation. This paper recommends targeted policy measures, including tax incentives for renewable energy technologies, regulatory reforms to support decentralized energy systems, and public-private partnerships (PPP) to mitigate financial risks in research and development. By addressing these challenges, the integration of CE and SEG can facilitate a transition to a sustainable, low-carbon future, benefiting both the environment and society.